THE FLOUTING OF GRICE’S CONVERSATIONAL MAXIMS BY THE MAIN CHARACTER IN THE DICTATOR MOVIE - ZULFA, ANNISA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study was conducted to identify the maxims flouted by the main character and the implicatures of the utterances containing maxims flouted by the main character in The Dictator movie. The researcher conducted a study on flouting maxims in Themovie since the communication happening between the Dictator main character and his interlocutors in the movie contains a lot of flouting of conversational maxims. Furthermore, this research used qualitative approach because the analysis is in the form of description rather than number. The results showed that the main character in the movie flouts all types of conversational maxims; maxim of quantity, maxim of quality, maxim of relation and maxim of manner. Then, the main character presents the implicature in several ways, such as by being more informative, making sure, agreeing or making jokes depending on the purpose and the situation under which the conversation occurs. From the findings above, we can conclude that through the flouted utterances produced, the main character shows and express various kind of flouting of Grice’s conversational maxims because he wants to deliver his implied meaning to his hearer. Keywords: Pragmatics, Cooperative Principle, Flouting Maxims, Implicatures, The Dictator Movie.